Effect of Punica Granatum (Pomegranate) on serum ALT and AST in Carbon tetrachloride induced liver damage in Wistar Albino Rats - Sadia, Halima; Akter, Qazi Shamima; Afroz, Rukhsana; Siddika, Tashfia (Journal of Bangladesh Society of Physiologist, 2016)
Background: Liver diseases are associated with significant morbidity and mortality. Punica granatum may have free radical scavenging activity and it can be used for the prevention and treatment of liver damage. Objective: To observe the hepatoprotective effects of Punica granatum on CCl4 induced liver damage in rats. Methods: The experimental study was carried out in the Dept of Physiology, Dhaka Medical Ccollege, Dhaka from July 2013 to June 2014. For this purpose, 36 wistar albino rats were studied. After acclimatization for 7 days, they were divided into two groups-control and experimental group. Control group were subdivided into BC (Baseline control), CC (CCl4 treated control) and SC (Silymarin treated control). Experimental group were subdivided into CP-APT (CCl4 pretreated and aqueous extract of pomegranate treated), CP-EPT (CCl4 pretreated and ethanolic extract of pomegranate treated) and APP-CT (Aqueous extract of pomegranate pretreated and CCl4 treated). Each sub group consisted of 6 rats. All rats received basal diet for 8 days. In addition to basal diet on 8th day, BC received single dose olive oil and CC received CCl4. Rats of SC received silymarin for 8consecutive days. In experimental groups, CP-APT received aqueous extract of Pomegranate and CP-EPT received ethanolic extract of Pomegranate for 8consecutive days. Moreover, APP-CT received aqueous extract of Pomegranate for 8 consecutive days and CCl4 only on 8th day. All rats were sacrificed on 9th day and then blood samples were collected. Serum ALT and AST levels were estimated by using standard laboratory kits. Statistical analysis was done one way ANOVA and Bonferroni test. Results: The mean serum AST and ALT levels were significantly (p<0.001) higher in CC in comparison to those of BC. Serum AST and ALT levels of all experimental groups were significantly (P<0.001) lower than CC. Silymarin used as a standard reference also exhibited significant hepatoprotective activity against CCl4 induced hepatotoxicity Conclusion: From the result of present study it can be concluded that, Pomegranate may have hepatoprotective effect by lowering ALT and AST levels Bangladesh Soc Physiol. 2016, June; 11(1): 23-28